T54R mutation destabilizes the dimer of superoxide dismutase 1T54R by inducing steric clashes at the dimer interface. Issue 18 (13th March 2020) - Ghosh, Debasish Kumar; Kumar, Abhishek; Ranjan, Akash
Abstract : T54R mutation destabilizes the dimer of SOD1 T54R . Abstract : Mutations cause abnormalities in protein structure, function and oligomerization. Different mutations in the superoxide dismutase 1 (SOD1) protein cause its misfolding, loss of dimerization and aggravate its aggregation in the amyotrophic lateral sclerosis disease. In this study, we report the mechanistic details of how a threonine-to-arginine mutation at the 54 th position (T54R) of SOD1 results in destabilization of the dimer interface of SOD1 T54R . Using computational and experimental methods, we show that the T54R mutation increases fluctuation of the mutation-harboring loop (R54-loop) of SOD1 T54R . Fluctuation of this loop causes steric clashes that involve arginine-54 (R54) and other residues of SOD1 T54R, resulting in loss of inter-subunit contacts at the dimer interface. Since the T54 residue-containing loop is necessary for the dimerization of wild-type SOD1, fluctuation of the R54-loop, steric clashes involving R54 and loss of inter-subunit contacts give rise to the loss of SOD1 T54R dimer stability. This correlates to energetically unfavorable tethering of the monomers of SOD1 T54R . The outcome is gradual splitting of SOD1 T54R dimers into monomers, thereby exposing the previously buried hydrophobic interface residues to the aqueous environment. This event finally leads to aggregation of SOD1 T54R . T54R mutation has no effect in altering the relative positions of copper and zinc ion binding residues of SOD1 T54R . The native SOD1 structure is stable, and there is no destabilizing effect at its dimer interface. Overall, our study reveals the intricate mechanism of T54R mutation-associated destabilization of the dimer of the SOD1 T54R protein.